1995
DOI: 10.1037/0022-3514.69.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Valence focus and arousal focus: Individual differences in the structure of affective experience.

Abstract: The structure of affect is well represented as a circumplex. The results of a within-subject longitudinal study of self-reported mood indicate individual differences in the circumplex structure of affective experience. These differences can be captured by two constructs: valence focus and arousal focus. Valence focus is the degree to which individuals attend the hedonic component of their affective experience; arousal focus is the degree to which individuals attend the arousal component of their affective expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
334
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(362 citation statements)
references
References 57 publications
20
334
0
8
Order By: Relevance
“…The dimensions represent the agreed-upon attributed or properties of the words (Davison, 1983). Coefficients of congruence with other solutions (depicting a cognitive structure for the same words derived from a different sample of similarity ratings ;Feldman, 1995;Feldman Barrett, 2004, Study 2) were above .90, indicating that the valence-arousal structure replicated at a group level. These findings replicated previous findings that emotion-related adjectives can be necessarily (but not sufficiently) defined in terms of the valence and the level of arousal they denote (Kring, Feldman Barrett, & Gard, 2003;Russell & Feldman Barrett, 1999).…”
Section: Resultsmentioning
confidence: 95%
“…The dimensions represent the agreed-upon attributed or properties of the words (Davison, 1983). Coefficients of congruence with other solutions (depicting a cognitive structure for the same words derived from a different sample of similarity ratings ;Feldman, 1995;Feldman Barrett, 2004, Study 2) were above .90, indicating that the valence-arousal structure replicated at a group level. These findings replicated previous findings that emotion-related adjectives can be necessarily (but not sufficiently) defined in terms of the valence and the level of arousal they denote (Kring, Feldman Barrett, & Gard, 2003;Russell & Feldman Barrett, 1999).…”
Section: Resultsmentioning
confidence: 95%
“…If attention to emotional experience influences emotion language, then the structure of emotion language will look different after experience sampling than it did before. This was not the case, however.Second, as in past research (Feldman, 1995a;Feldman Barrett, 1998), people differed in the extent to which they emphasized valence-and arousal-based information in their verbal reports of emotional experience. Some people reported their feelings with more pleasure and displeasure than did others.…”
mentioning
confidence: 80%
“…Each participant's P-correlation matrix can be factor analyzed; the first two unrotated factors extracted are typically valence and arousal, and the size of each factor represents the variance in the self-report ratings accounted for by each property. The factor-analytic estimates of valence focus and arousal focus, although strongly related to the more externally based estimates (Feldman, 1995a;Feldman Barrett, 1998), are less optimal because they contain the usual ambiguities associated with factor analysis (such as factor identification). resulting indices are themselves correlation coefficients, they too were subjected to a Fisher's r-to-z transformation before being used in further analyses.…”
mentioning
confidence: 99%
“…9 An inspection of the solution suggested that one axis corresponded to the arousal denoted by the affect terms, and the other corresponded to valence. The congruence coefficients for this solution and those used in Study 1 (taken from Feldman, 1995) were .94 for the arousal dimension and .92 for the valence dimension. This group solution produced the arousal-based semantic distance matrix used to compute AF.…”
Section: Methodsmentioning
confidence: 96%
“…: The external criterion that we used to compute AF was based on the cognitive structure of emotion language. The structure used here was derived from a previously published multidimensional scaling (MDS) solution of similarity judgments for the same 16 emotion-related words used to compute the pcorrelation matrices (Feldman, 1995). Similarity judgments for emotion-related words, when subjected to an MDS analysis, routinely yield valence and arousal dimensions that represent the basic, semantic properties contained in our knowledge about those words and the concepts they represent.…”
Section: Estimating Arousal Focusmentioning
confidence: 99%